Prevalencia de Ansiedad y Depresión por COVID-19 en el Personal de Enfermería - Rodríguez Alejandro, Olvera; Ledesma Edith, González; Joaquín Emmanuel, Frías Benítez; Alma Argelia, Fierro Muñoz; Palomé-Vega, Gabriela (European Scientific Journal, ESJ, 2023)
Introducción. El personal de enfermería que labora en el segundo nivel de atención enfrenta diariamente situaciones que pueden afectar su salud mental como la depresión y la ansiedad. Algunos de los factores que incrementan la incidencia de estos son: el aumento de casos de COVID-19 y la saturación de los servicios sanitarios. Objetivo. Medir la prevalencia de ansiedad y depresión por COVID-19 en el personal de enfermería, de un hospital de segundo nivel de atención. Metodología. Estudio con enfoque cuantitativo, con un diseño descriptivo y corte transversal. Mediante un muestreo estadístico por fórmula, se aplicó la Escala de Ansiedad y Depresión de Goldberg (EADG) a 45 integrantes del personal de enfermería; fueron considerados los principios bioéticos en los participantes que aceptaron firmar la carta de consentimiento informado. Resultados. La media de edad fue de 33.67 años y el 62% presenta la ansiedad y con respecto a la variable depresión, no se presentó; sin embargo, se manifiestó un riesgo del 20% de los participantes de presentar síntomas de depresión, entre los que se identificaron: dificultad para concentrarse, pérdida de apetito, sentirse aletargado y despertar demasiado temprano. Conclusiones. Abordar la salud mental en el personal de enfermería es de sumo interés, dado que la presencia de estos padecimientos puede afectar desde la salud del trabajador, hasta la atención y el cuidado que se les brinda a los pacientes. Introduction. Nursing staff working in the second level of hospital care face daily situations that can affect their mental health, leading to conditions such as depression and anxiety. Some of the factors that increase the incidence of these are: the increase in cases of COVID-19, little certainty in the information on the treatment and care of this disease, the saturation of health services, shortage of supplies, lack of assistance personnel, long working hours, and the mortality rate of the population. Objective. To measure the prevalence of anxiety and depression due to COVID-19 in the nursing staff of a second-level care hospital in the state of Querétaro, in order to obtain information that allows, subsequently, to create strategies for the care of nursing staff. Methodology. A study of quantitative approach, descriptive level and cross section was carried out. A statistical sampling by formula defined the sample of 45 members of the nursing staff; Data collection was used by Goldberg Anxiety and Depression Scale (EADG) with 18 items with dichotomous response. Bioethical principles were considered and participants were asked to accept the signing of the informed consent letter. Descriptive statistics were used in the analysis of information by means of averages. Results. The mean age was 33.67 years and in terms of the prevalence of anxiety, is present in 62% of the sample and with respect to the variable depression, there is no presence of this; however, there is a risk of 20% of the sample to have symptoms of depression, among which were identified: difficulty concentrating, loss of appetite, feeling elongated and waking up too early. Conclusions. Addressing mental health in nursing staff is of great interest, as the presence of these conditions can affect from the health of the worker to the care and care provided to patients.